Expert System Of Nose Disease With Hybrid Method - Yogi Wiyandra; Firna Yenila (Universitas Dian Nuswantoro and IndoCEISS, 2019)
Nasal disease is a type of disease that is classified as often afflicting someone. And it is not uncommon among people to conduct a direct examination on ENT specialists to find out the type of disease they are experiencing. Thus an alternative is needed to find out early the problems that arise from the nose. The intended alternative is to build a system in the form of an expert system that uses one's expertise in providing knowledge in the form of a nose condition. The system was built using a hybrid method that combines the forward chaining method and the certainty factor. So, the results or knowledge given to the public is confirmed by the percentage given.